LAJU INFILTRASI DAN BEBERAPA SIFAT TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI DESA DADAKITAN KECAMATAN BAOLAN KABUPATEN TOLI-TOLI - Andi Idham M; Uswah Hasanah; syamsul Syukur (Fakultas Pertanian, Universitas Tadulako, 2022)
The present study was designed to investigate the infiltration rate and various soil properties of different land uses in Dakitan village, Baolan sub district, Toli-Toli district. The study was carried out over a period of fifteen months, starting from March 2020 and ending in June 2021. The research involved the determination of infiltration rate, soil texture, soil bulk density, soil porosity, field capacity water content, organic matter, and aggregate stability in four types of land use, namely mixed plantations, a clove plantation, and a secondary forest, all of which had varying slope angles. The results of the study indicate that the constant infiltration rate across several land uses was ranging from 15.59-180.62 mm h-1, which were classified as slow to fast. The soil texture was predominantly sandy clay, while the organic matter was classified as high to very high (4.03-6.02%). The soil bulk density was found to be heavy (1.24 –1.65 g cm-1), and the porosity ranged from 26.37-42.98%. The field capacity water content was found to range from 21.93-43.16%, and the aggregate stability was predominantly unstable.